The Value of Preventing Malaria in Tembien, Ethiopia - Cropper, Maureen L.; Haile, Mitiku; Lampietti, Julian A.; Poulos, Christine; Whittington, Dale (World Bank, Washington, DC, 2015)
The authors measure the monetary value households place on preventing malaria in Tembien, Tigray Region, Ethiopia. They estimate a household demand function for a hypothetical malaria vaccine and compute the value of preventing malaria as the households maximum willingness to pay to provide vaccines for all family members. They contrast willingness to pay with the traditional costs of illness (medical costs and time lost because of malaria). Their results indicate that the value of preventing malaria with vaccines is about US$36 a household a year, or about 15 percent of imputed annual household income. This is, on average, about two or three times the expected household cost of illness. Despite the great benefits from preventing malaria, the fact that vaccine demand is price inelastic suggests that it will be difficult to achieve significant market penetration unless the vaccine is subsidized. The authors obtain similar results for insecticide-treated bed nets. Their estimates of household demand functions for bed nets suggest that at a price that might permit cost recovery (US$6 a bed net), only a third of the population of a 200-person village would sleep under bed nets.